PENERAPAN PENDEKATAN KETERAMPILAN DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PEAJARAN FIQH KELAS 2 DI MA MUHAMMADIYAH - Zulkifli Zulkifli (Fitrah, 2023)
This research is to find out the application of the skills approach in improving student learning outcomes in fiqh subjects, this research uses a type of qualitative research with a descriptive approach, this research uses data collection methods through observation, interviews and documentation with data collection techniques through four stages, namely data collection, reduction data, display data, and conclude. The results of the application of skills to fiqh material using a skills approach, namely by practicing in terms of worship, and through extracurricular activities, this can be seen that every time of prayer, especially the Duha prayer, it is recommended that all students perform midday prayers together, take ablution water in an orderly manner.